Dynamic estimation of soft tissue stiffness for use in modeling socket, orthosis or exoskeleton interfaces with lower limb segments. (March 2022) - Guitteny, Sacha; Lafon, Yoann; Bonnet, Vincent; Aissaoui, Rachid; Dumas, Raphael
Abstract: Modeling the interface between the lower limb segments and a socket, orthosis or exoskeleton is crucial to the design, control, and assessment of such devices. The present study aimed to estimate translational and rotational soft tissue stiffness at the thigh and shank during daily living activities performed by six subjects. Smooth orthogonal decomposition (SOD) was used on skin marker trajectories and fluoroscopy-based knee joint kinematics to compute stiffness coefficients during squatting, sitting and rising from a chair, level walking, and stair descending. On average, for all subjects and for all activities, in the anatomical directions observed, the translational and rotational stiffness coefficients for the shank were, respectively, 1.4 ± 1.99kN/m (median and interquartile range) and 41.5 ± 34.3Nm/deg. The results for the thigh segment were 1.79 ± 2.73kN/m and 30.5 ± 50.4Nm/deg. As previously reported in the literature dealing with the soft tissue artifact – considered as soft tissue deformation in this study - the computed stiffness coefficients were dependent on tasks, subjects, segments, and anatomical directions. The main advantage of SOD over previous methods lies in enabling estimation of a task-dependent 6 × 6 stiffness matrix of the interface between segments and external devices, useful in their modeling and assessment.